The Effectiveness of Awards by Leaders on the Achievement of Work of Government Apparatus In Dimembe Subdistrict of North Minahasa Regency - Rumapea, Prof. Dr. Drs. Patar; Daicy Jetty Lengkong, Florence (IJRDO - Journal of Social Science and Humanities Research, 2017)
The purpose of this study was to clarify the effect of the effectiveness of the award by the leader on the performance of government officials. This research took place in Kecamatan Dimembe involving 80 respondents from three sample villages: Dimembe Village, Warukapas Village, Wasian Village and Dimembe District Office. This research uses a quantitative research approach with descriptive analysis techniques and simple linear regression analysis. Based on the results of the research show that: (1) the results of descriptive analysis shows that the effectiveness of the leadership award at the high category, while the performance of government officials in middle category. (2) hasdil these simple linear regression analysis showed that the effectiveness of the award by the leader on the performance of government officials working in the district Dimembe positive and significant impact. Based on the results of the analysis, it can be concluded that the work performance of the government apparatus in Kecamatan Dimembe is determined by the effectiveness of awarding by leaders in the high category. It is suggested to the Head of Sub-district as the leader and government officials to pay attention to the giving of pernghargaan to the apparatus who excel in the work